(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article is devoted to the development of a probabilistic approach to assessing the fault tolerance of distributed data storage models on the servers of major religious organizations. A review of existing software tools for monitoring the health of data storage systems in religious organizations was carried out, the approaches used for data collection, processing and storage were identified, the tools used to identify failures were described, and the features ro is listed.